Câmbio, especulação e juros no modelo da Teoria Geral - Sicsú,João (2008)
This short chapter aims to make an adaptation to a small and financially integrated economy of the monetary / financial model presented by J. M. Keynes in his General Theory of Employment, interest and money. So, this has as a goal, particularly, to adapt the chapters 15 and 17 of the General Theory basically concerned to the speculative motivations to define the composition of the assets portfolio.